A closer look on the effectiveness of the EU legal framework for excessive pricing during the COVID-19 crisis. Issue 1 (2nd January 2022) - Basaran, Bahriye
ABSTRACT: The unanticipated global mass panic that has arisen as a result of the rapid spread of the COVID-19 has had a major impact on the functioning of many markets. Many competition authorities around the world have faced with excessive pricing practices due to the dramatic price hikes of essential items, ranging from personal and medical equipment to basic food products particularly at the onset of the pandemic. The crisis has not been just about pricing, whether the public or the state is willing to pay for certain products or not; at the heart of the problem, there has been a sudden sharp asymmetry between the supply and demand. Based on this asymmetry, this article, by acknowledging that Article 102 (a) fails to deliver a swift and efficient response to this crisis due to conceptual and practical difficulties in its application, addresses other ways that competition authorities and governments use to deal with the virus-profiteers.